Media Pembelajaran Kamus Tiga Bahasa Dayak Ngaju – Indonesia – Dayak Ma’anyan Berbasis Web: Development of a Web-Based Trilingual Dictionary Learning Media for Dayak Ngaju, Indonesian, and Dayak Ma’anyan - Rosmiati Rosmiati; Siti Maryamah; Suparno Suparno; Rudini Rudini (Jurnal Sains Komputer dan Teknologi Informasi, 2026)
Language is a fundamental means of communication that plays an essential role in society. In addition to the Indonesian language, the Indonesian nation possesses a rich diversity of regional languages that may be difficult for some communities to understand. Among these are the Dayak Ngaju and Dayak Ma’anyan languages. Currently, there is no officially published dictionary for the Dayak Ma’anyan language. Therefore, it is necessary to develop an application that incorporates local languages spoken in Palangkaraya, particularly the Dayak Ngaju and Dayak Ma’anyan languages, in order to help the community understand and learn these regional languages. The system development employed an experimental method consisting of system planning, program development, and result testing. The system was developed using the PHP programming language and a MySQL database, while Macromedia Dreamweaver was used for program design. The testing results indicate that the system is capable of translating words or sentences from Indonesian into Dayak Ngaju and Dayak Ma’anyan, from Dayak Ngaju into Dayak Ma’anyan and Indonesian, and from Dayak Ma’anyan into Dayak Ngaju and Indonesian